Aryl C-glycosylation of phenols with glycosyl trifluoroacetimidates - Li, Y.; Wei, G.; Yu, B.
Aryl C-glycosylation of a variety of phenols with glycosyl trifluoroacetimidates in the presence of TMSOTf was examined, leading to the corresponding ortho-hydroxyaryl C-glycosides in variable yields.
Keywords: C-GLYCOSYLATION; ARYL C-GLYCOSIDES; GLYCOSYL TRIFLUOROACETIMIDATES; PHENOLS